2002
DOI: 10.1097/00005344-200206000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Imidazoline Receptors in the Heart: Characterization, Distribution, and Regulation

Abstract: Imidazoline receptors were identified in cardiac tissues of various species. Imidazoline receptors were immunolocalized in the rat heart. Membrane binding and autoradiography on frozen heart sections using 0.5 nM para-iodoclonidine (125I-PIC) revealed that binding was equally and concentration-dependently inhibited by epinephrine and imidazole-4-acetic acid (IAA), implying 125I-PIC binding to cardiac alpha2-adrenergic and I1-receptors, respectively. After irreversible blockade of alpha2-adrenergic receptors, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
29
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 31 publications
6
29
0
Order By: Relevance
“…Compared to age-matched normotensive Wistar Kyoto rats, I 1 -receptor Bmax was 2-fold (P < 0.01) higher in 12-week-old SHR right and left atria, but not altered in ventricles. Compared to corresponding normal controls, Bmax was 2-fold higher (P < 0.01) in ventricles of hamsters with advanced cardiomyopathy and in human ventricles with heart failure ( Figure 1) (15). We also demonstrated that cardiac I 1 -receptors, but not α2-adrenoceptors, are regulated by chronic in vivo exposure to the I 1 -receptor selective ligand, moxonidine.…”
Section: Cardiac Imidazoline I 1 -Receptorssupporting
confidence: 52%
See 2 more Smart Citations
“…Compared to age-matched normotensive Wistar Kyoto rats, I 1 -receptor Bmax was 2-fold (P < 0.01) higher in 12-week-old SHR right and left atria, but not altered in ventricles. Compared to corresponding normal controls, Bmax was 2-fold higher (P < 0.01) in ventricles of hamsters with advanced cardiomyopathy and in human ventricles with heart failure ( Figure 1) (15). We also demonstrated that cardiac I 1 -receptors, but not α2-adrenoceptors, are regulated by chronic in vivo exposure to the I 1 -receptor selective ligand, moxonidine.…”
Section: Cardiac Imidazoline I 1 -Receptorssupporting
confidence: 52%
“…Moxonidine (120 µg kg -1 h -1 ) decreased (P < 0.01) I 1 -receptor Bmax in right and left atria to normal levels (Figure 2), without altering α2-adrenoceptor Bmax. These results showed for the first time that imidazoline I 1 -receptors and α2-adrenoceptors are present in heart atria and ventricles, and that only imidazoline I 1 -receptors are responsive to changes in the cardiovascular environment and to chronic exposure to the I 1 -selective agonist, moxonidine (15,16). These results implicate heart imidazoline I 1 -receptors in cardiovascular regulation.…”
Section: Cardiac Imidazoline I 1 -Receptorsmentioning
confidence: 57%
See 1 more Smart Citation
“…I 1 -receptors are mainly found in the brainstem, adrenal chromaffin cells, and kidneys. In addition, we have recently identified I 1 -receptors in heart atria and ventricles and shown that atrial I 1 -receptors are up-regulated in rat hypertension and ventricular I 1 -receptors are up-regulated in human and hamster heart failure (El-Ayoubi et al, 2002a). In other studies, we demonstrated that acute injections of moxonidine, an imidazoline compound that shows 40 times higher affinity to I 1 -receptor versus ␣ 2 -adrenoceptors, are associated with enhanced release of atrial natriuretic peptide (Mukaddam-Daher and Gutkowska, 2000), a cardiac hormone involved in pressure and volume homeostasis.…”
mentioning
confidence: 99%
“…Imidazoline receptors were identified in the pancreas, central nervous system (CNS), kidneys and heart (El-Ayoubi et al 2002, Narahashi 2000. Two subtypes of imidazoline receptors were found: I 1 (controls the central regulation of blood pressure) and I 2 (has neuroprotective function for cerebral ischemia (Greney et al 2000, Nicolic et al 2009).…”
Section: Introductionmentioning
confidence: 99%